Factors Affecting Early Detection and Stimulation by Mothers and their Impact on Receptive Language Skills of Children Age 4 to 6 Years - Putri, Anggi Resina; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: